2016
DOI: 10.1128/jvi.03079-15
|View full text |Cite
|
Sign up to set email alerts
|

Bat Severe Acute Respiratory Syndrome-Like Coronavirus WIV1 Encodes an Extra Accessory Protein, ORFX, Involved in Modulation of the Host Immune Response

Abstract: Bats harbor severe acute respiratory syndrome (SARS)-like coronaviruses (SL-CoVs) from which the causative agent of the 2002-2003SARS pandemic is thought to have originated. However, despite the fact that a large number of genetically diverse SL-CoV sequences have been detected in bats, only two strains (named WIV1 and WIV16) have been successfully cultured in vitro. These two strains differ from SARS-CoV only in containing an extra open reading frame (ORF) (named ORFX), between ORF6 and ORF7, which has no hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 34 publications
1
74
0
3
Order By: Relevance
“…Coupled with the augmented replication and protein production of wild-type MERS-CoV in the presence of trypsin, the results suggest that the proteolytic cleavage epidemic MER-CoV could still be enhanced, potentially by augmenting the cell surface entry mechanism, as previously described for SARS-CoV (42). While group 2B bat CoV strains (WIV1-CoV, WIV16-CoV, and SHC014-CoV) do not require trypsin for infection (9,13,14,43), differences in protease activation may contribute to infection changes relative to the epidemic SARS-CoV. In this context, our findings expand the importance of protease cleavage as a criterion to consider for zoonotic virus emergence in a new host population.…”
Section: Discussionsupporting
confidence: 54%
“…Coupled with the augmented replication and protein production of wild-type MERS-CoV in the presence of trypsin, the results suggest that the proteolytic cleavage epidemic MER-CoV could still be enhanced, potentially by augmenting the cell surface entry mechanism, as previously described for SARS-CoV (42). While group 2B bat CoV strains (WIV1-CoV, WIV16-CoV, and SHC014-CoV) do not require trypsin for infection (9,13,14,43), differences in protease activation may contribute to infection changes relative to the epidemic SARS-CoV. In this context, our findings expand the importance of protease cleavage as a criterion to consider for zoonotic virus emergence in a new host population.…”
Section: Discussionsupporting
confidence: 54%
“…Although coronavirus accessory proteins are not essential for virus replication in vitro (Casais et al, 2005;Yount et al, 2005), previous reports have made it clear that these accessory proteins are not redundant, but rather possess many functions, including modulating viral pathogenicity (De Haan et al, 2002) and acting as cell death inducers (Law et al, 2005) or interferon antagonists (Niemeyer et al, 2013;Siu et al, 2014). Furthermore, recent studies have reported the discovery of novel accessory proteins in some coronaviruses, such as the newly identified accessory protein ORFX of bat severe acute respiratory syndrome-like coronavirus (Zeng et al, 2016). For deltacoronavirus, no information on the expression, intracellular localization, function of accessory proteins or on their unique sgRNAs has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Since its first discovery in Chinese horseshoe bats in 2004 , SARSr-CoVs have been continuously found in various horseshoe bat species in the last 13 years (Drexler et al, 2010;Ge et al, 2013;He et al, 2014;Hu et al, 2017;Lau et al, 2005;Lau et al, 2010a;Li et al, 2005a;Tang et al, 2006;Wu et al, 2016;Yang et al, 2013;Yang et al, 2015;Zeng et al, 2016). This is in contrast to the case for civets and human, where SARSr-CoVs were only found in 2003/2004, and never reported afterward.…”
Section: Circulation Of Sarsr-cov In Horseshoe Bats In 2004 To 2018mentioning
confidence: 93%